Investigating metabolic regulation of livestock skeletal muscle - Rimmer, Linnea Ann (My University, 2026)
Global population growth and shifts in dietary preferences, particularly in developing regions, have placed unprecedented pressure on the livestock industry to increase lean muscle production. Concurrently, reductions in available arable land require animal production systems to generate greater outputs while utilizing fewer resources. As a result, improving livestock efficiency remains a critical priority for sustaining future agricultural productivity. Skeletal muscle plays a central role in feed efficiency and overall productivity, accounting for approximately 45% of an animal’s body mass and consuming the majority of dietary glucose. This highly dynamic tissue is composed of muscle fibers with distinct metabolic profiles that influence nutrient utilization, energy production, and growth potential. Therefore, the objective of this dissertation was to determine how genetic variation alters skeletal muscle metabolism and regulates substrate partitioning between glycolytic and oxidative pathways. To address this objective, two unique animal models were utilized across bovine and porcine species. Skeletal muscle was collected from muscles representing a range of metabolic phenotypes, including the longissimus dorsi (LD; glycolytic), latissimus dorsi (LAT; mixed), semitendinosus (ST; mixed), and masseter (MS; oxidative). The first study investigated cattle harboring a naturally occurring mutation in the glycogen myophosphorylase PYGM gene, commonly referred to as “PYGM cattle,” to determine how impaired glycogenolysis influences downstream metabolism. In this model, restricted glycogen breakdown altered pyruvate metabolism through shifts in lactate dehydrogenase (LDH) isoform abundance. Specifically, LDH[alpha] abundance increased in whole muscle preparations from the LD and MS of PYGM cattle compared to control cattle (p < 0.05); while mitochondrial fraction preparations increased the abundance of LDH[beta] in PYGM cattle regardless of muscle (p < 0.05). Although pyruvate entry into the tricarboxylic acid (TCA) cycle via pyruvate dehydrogenase (PDH) did not differ between genotypes (p > 0.05), pyruvate carboxylase (PC) abundance increased in the LD and LAT muscles of PYGM cattle (p < 0.05). Collectively, these findings indicate a shift in pyruvate partitioning toward anaplerotic pathways to support mitochondrial metabolism under conditions of limited glycogen availability. The second study examined a pig model that was specifically bred to be heterozygous for two naturally occurring mutations in key metabolic genes. One mutation in the ryanodine receptor gene (RYR1), which is associated with the halothane-sensitivity locus “(HAL).” A second mutation in the PRKAG3 gene, which regulates AMP-activated protein kinase gamma subunit (AMPK[gamma]) and is referred to as an “RN” mutation. The HAL mutation alters calcium handling in skeletal muscle, promoting a more glycolytic phenotype; however, this mutation is also associated with adverse effects on animal survivability and meat quality at slaughter. The RN mutation alters cellular energy sensing through regulation of AMP and ADP levels, resulting in constitutive activation of AMPK and promoting a more oxidative skeletal muscle phenotype. In contrast to the PYGM cattle model, LDH[alpha] abundance did not differ among genotypes (p > 0.05), whereas LDH[beta] abundance decreased in the MS muscle of WT, RN, and RN-HAL pigs compared to all other muscles within each genotype (p < 0.05). Additionally, no differences were observed in PDH or PC abundance among genotypes (p > 0.05). These data suggest that nutrient partitioning and handling still differs even when substrates are not limited. Collectively, these studies demonstrate that genetic variation alters skeletal muscle metabolism by regulating pyruvate fate, thereby influencing substrate partitioning between glycolytic and oxidative pathways. Overall, this work provides new insight into the metabolic mechanisms underlying nutrient utilization and mitochondrial function, with implications for improving feed efficiency, enhancing muscle growth, and advancing sustainability in livestock production systems.
Keywords: Skeletal muscle; Metabolism; Mitochondria; Growth